IDEA REPRESENTATION AND SUMMARIZING STRATEGIES IN ARTICLE SUMMARIES WRITTEN BY INDONESIAN EFL STUDENTS - Bambang Yudi Cahyono; Shirly Rizki Kusumaningrum (Universitas Katolik Indonesia Atma Jaya, 2015)
This study examined idea representation and summarizingstrategies in article summaries written by Indonesian EFLstudents. When the study was conducted, the students wereattending a graduate course on “the Teaching of Writing” in theGraduate Program in ELT at State University of Malang,Indonesia. This study describes the students’ article summariesin terms of idea representation based on the ICF (‘introduction,’‘content,’ and ‘finalization’) frame and strategies applied in thearticle summaries. Data in the form of article summaries writtenby 16 students were collected at the end of the course. Theresults of data analysis show that most of the Indonesian EFLstudents could successfully represent the the ideas from thejournal articles into their summaries. However, not all of thestudents consider that ‘finalization’ component in the frameneeds to be included in their summaries. In terms of strategies insummarizing, most of the students made summaries by copyingideas and words with no or some modification, whereas onlysome of them write summaries by using their own expressions.This means that the students found that summarizing is not aneasy task. Therefore, this study recommends EFL teachers toteach their students strategies to summarize successfully. It alsoencourages EFL teachers to remind the students to use their ownexpressions in their article summaries in order to avoidplagiarism.Keywords: Idea representation; strategies in summarizing;article summaries; journal articles; IndonesianEFL students